Ecolabelling, certification and accreditation : elements of a possible model for the ecotourism industry in southern and eastern Africa - Pina, Ralph Felix (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPhil (Geography and Environmental Studies))--University of Stellenbosch, 2004.